PENGARUH SUBTITUSI ABU CANGKANG TELUR PADA MORTAR GEOPOLIMER - Tunnisa, Rizki Khoiriah; Firdaus, Firdaus (Ensiklopedia of Journal, 2024)
The aim of this research was to determine the effect of eggshell ash substitution in geopolymer mortar on the setting time and compressive strength of geopolymer mortar with variations in the eggshell ash mixture of 0%, 5%, 10% and 15% at ages 7, 14 and 28. day.   This research includes testing the compressive strength of geopilimer mortar and setting time. The setting time test was carried out using a vicat tool with ASTM C 191-08 standard, the test was carried out according to the planned mixture variations. And the compressive strength test was carried out after the geopolymer mortar reached 7, 14 and 28 days with the test object size being 5mm x 5mm x 5mm. Research data indicates that eggshell ash material has an influence on geopolymer mortar with certain mixture variations. The fastest setting time test was obtained with a variation of 15% with the initial setting time at 195 minutes and the final setting time at 225 minutes. In the compressive strength test results of 5% variation of geopolymer mortar, the highest compressive strength values were obtained, reaching 7.73 Mpa after 7 days, 10.67 Mpa after 14 days, and 16.4 Mpa after 28 days. Keywords: Geopolymer mortar, eggshell ash, setting time, and compressive strength